Qualitative Study of Factors Causing Double Numbering of Medical Record Documents at Dharma Yadnya Hospital Denpasar - Ni Luhtu Rediyantini; Purwanti, Ika Setya; Widana, A. A. Gde Oka (Basic and Applied Nursing Research Journal, 2023)
Introduction: Duplication is when two medical record numbers have the same identity or patient. Duplication or double numbering of medical records occurs because the patient's medical record file is not found when the patient comes for treatment, or the patient needs to remember to bring the Medical Index Card (MIC). This study wanted to determine the factors that cause duplication or double numbering of medical record documents. Method: Data collection was carried out by in-depth interviews, observation, and documentation using case study research with qualitative descriptive methods. The Miles and Huberman method is used in data analysis. The sample of this study amounted to 5 people with purposive sampling techniques. Results: The results of the study showed that the implementation of medical record documents in the registration section uses a computerized system, numbering system using the Unit Numbering System (UNS), alignment system using the Straight Numerical Filling (SNF) system, storage system using a Decentralized system, and the leading cause of duplication of medical record numbers at Dharma Yadnya Hospital is that when patients come for treatment often do not bring MIC or other identity cards. Conclusion: From the study results, the implementation of taking medical record documents has not followed the Standard Operational Procedure (SOP) because it has yet to implement tracers. So, tracers are recommended, and officers must be careful in carrying out health services following existing SOP regulations.